Combination of selenium‐enriched green tea polysaccharides and Huo‐ji polysaccharides synergistically enhances antioxidant and immune activity in mice. (1st July 2015) - Yuan, Chengfu; Li, Zhihong; Peng, Fan; Xiao, Fangxiang; Ren, Dongming; Xue, Hui; Chen, Tao; Mushtaq, Gohar; Kamal, Mohammad Amjad
Abstract: BACKGROUND: The aim of this study was to investigate the influence of a combination of selenium‐enriched green tea polysaccharides (Se‐GTP) and Huo‐ji polysaccharides (HJP) on the immune function and antioxidant activity in mice. RESULTS: The results showed that the indices of spleen and thymus were markedly increased, and the activity of natural killer (NK) cell was promoted in mice treated with the combination of Se‐GTP and HJP. The combined treatment of Se‐GTP and HJP also reduced the content of tumour necrosis factor‐α (TNF‐α) and interleukin‐6 (IL‐6) in splenocytes. In addition, the activities of glutathione peroxidase (GPx) and superoxide dismutase (SOD) were remarkably enhanced, and malondialdehyde (MDA) levels were significantly reduced in mice treated with combination of Se‐GTP and HJP. Furthermore, the combined treatment of Se‐GTP and HJP increased nuclear factor erythroid 2‐related factor (Nrf2) expression at mRNA and protein levels in splenocytes. The effects of the combination treatment of Se‐GTP and HJP in mice were stronger than with Se‐GTP or HJP treatment alone. CONCLUSION: Our study suggests that the combined administration of Se‐GTP and HJP can synergistically improve immune function and decrease the oxidative stress by enhancing the mechanisms involved in the clearance of free radicals. © 2015 Society of Chemical Industry